2020
DOI: 10.34305/nnc.v1i1.134
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Gaya Kepemimpinan Kepala Ruangan Dengan Motivasi Kerja Perawat Di Ruang Rawat Inap Rumah Sakit Kuningan Medical Center

Abstract: Kepemimpinan merupakan cara seorang pemimpin dalam mempengaruhi perilaku bawahannya agar mau bekerja sama dan bekerja secara produktif  dei tercapainya tujuan dari organisasi. Gaya kepemimpinan suatu seni dan proses untuk mempengaruhi dan mengarahkan orang lan agar mereka memiliki motivasi untuk mencpai tujuan yang hendak di capai dalam situasi tertentu. Tujuan penelitian ini mengetahui hubungan gaya kepemimpinan kepala ruangan dengan motivasi kerja perawat di ruang rawat inap rumah sakit kuningan medical cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
1
1
Order By: Relevance
“…Education Level is also a learning process where it can increase or improve one's education so that it can increase knowledge and information (Astuty, 2011) Variavel Frequency Distribution of Leadership Styles Table 2 of the results showed that the head of the room was dominant in the Democratic leadership style with a total of 48 respondents with a percentage (27%). The results of this study are different from the results of research conducted by Meria Kontesa (Kontesa, 2014), with a total of 38 respondents with a percentage (44.7%). According to the theory of Lippits & K. White (2015), said that the democratic leadership style is where the leader gives opportunities and values subordinates and includes bahawan in every decision to be taken.…”
Section: Character Of Respondent's Education Levelcontrasting
confidence: 99%
See 1 more Smart Citation
“…Education Level is also a learning process where it can increase or improve one's education so that it can increase knowledge and information (Astuty, 2011) Variavel Frequency Distribution of Leadership Styles Table 2 of the results showed that the head of the room was dominant in the Democratic leadership style with a total of 48 respondents with a percentage (27%). The results of this study are different from the results of research conducted by Meria Kontesa (Kontesa, 2014), with a total of 38 respondents with a percentage (44.7%). According to the theory of Lippits & K. White (2015), said that the democratic leadership style is where the leader gives opportunities and values subordinates and includes bahawan in every decision to be taken.…”
Section: Character Of Respondent's Education Levelcontrasting
confidence: 99%
“…The results of Aiken's research (Aiken et al, 2012) show that many nurses are less motivated than leaders and this can lead to poor nurse services. Lack of communication and motivation from the head of the room towards work performance, nurses feel uninspired to carry out work, feel dissatisfied with problems with the emphasis of the work done, (Siagian, 1991) The results of Kontesa's research (Kontesa, 2014), with the title of the relationship between the leadership style of the head of the room with the work motivation of nurses in the inpatient room of Dr. Rasiding padang., with the results showing that the head of the room uses Democratic leadership styles (44.7%), orthocratic (34.2), participatory (18.4%), laisses-faire (2.6%). And moderate nurse work motyivation (44.1%), high motivation (38.4%), less motivation (17.6%).…”
Section: Introductionmentioning
confidence: 99%